A Comprehensive Review of the Pharmacodynamics, Pharmacokinetics, and Clinical Effects of the Neutral Endopeptidase Inhibitor Racecadotril - Eberlin, Marion; Mück, Thomas; Michel, Martin C. (Frontiers in Pharmacology, 2012)
Racecadotril, via its active metabolite thiorphan, is an inhibitor of the enzyme neutral endopeptidase (NEP, EC 3.4.24.11), thereby increasing exposure to NEP including enkephalins and atrial natriuretic peptide. Upon oral administration racecadotril is rapidly and effectively converted into the active metabolite thiorphan, which does not cross the blood-brain-barrier. Racecadotril has mainly been tested in animal models and patients of three therapeutic areas. As an analgesic the effects of racecadotril across animal models were inconsistent. In cardiovascular diseases such as hypertension or congestive heart failure results from animal studies were promising, probably related to increased exposure to atrial natriuretic peptide, but clinical results have not shown substantial therapeutic benefit over existing treatment options in cardiovascular disease. In contrast, racecadotril was consistently effective in animal models and patients with various forms of acute diarrhea by inhibiting pathologic (but not basal) secretion from the gut without changing gastro-intestinal transit time or motility. This included studies in both adults and children. In direct comparative studies with loperamide in adults and children, racecadotril was at least as effective but exhibited fewer adverse events in most studies, particularly less rebound constipation. Several guidelines recommend the use of racecadotril as addition to oral rehydration treatment in children with acute diarrhea.